In vivo evaluation of the anti-obesity effects of combinations of Monascus pigment derivatives. Issue 3 (8th January 2020) - Choe, Deokyeong; Jung, Hyun Ho; Kim, Daehwan; Shin, Chul Soo; Johnston, Tony Vaughn; Ku, Seockmo
Abstract : The combination of threonine and tryptophan derivatives of Monascus pigment showed the high anti-obesity effect in mice. Abstract : The prevention and treatment of obesity using naturally derived compounds is desirable in terms of marketing and safety in the nutraceutical and functional food markets. One of the noticeable effects of Monascus pigment derivatives is the inhibition/deactivation of lipid metabolism. Our earlier studies reported that threonine (Thr), tryptophan (Trp), and 2-( p -tolyl)-ethylamine (TEA) derivatives of Monascus pigment showed cholesterol-lowering, lipase-inhibitory, and adipogenic differentiation-inhibitory activities, respectively. In this work, we investigated the in vivo anti-obesity effects of a combination of Thr, Trp and TEA derivatives. C57BL/6 mice were fed a high-fat diet (HFD) and simultaneously administered one of three 1 : 1 mixtures of Thr, Trp, and TEA derivatives. After 10 weeks of feeding, the weight gains of mice fed with three combined derivatives decreased by 20.3–37.9%, compared to mice fed the HFD. The epididymal adipose tissue (EAT) weights of mice fed with the combined derivatives decreased by 42.3–60.5% compared to the HFD group, and their EAT size decreased. Transverse micro-CT imaging revealed reduction of the subcutaneous and visceral fat layers of test mice. Our results confirm that Monascus -fermented pigment derivatives have in vivo anti-obesity effects and their combinations provide a higher efficacy in the reduction of body weight and EAT weights as well as lipid accumulation in mice. The key to accomplishing high anti-obesity effect was combining Thr and Trp derivatives, which provide higher effectiveness than other combined derivatives. These observations offer a potential use of Monascus pigment derivatives as a therapeutic approach to prevention and/or treatment of obesity.